Some Aspects Of Open Fractures Of Long Bones - K. Kh. Mamadjonov (Genius Journals, 2024)
Open fractures of the long bones of the extremities are among the most severe injuries to the musculoskeletal system. The article discusses the classification of open fractures of long bones
Keywords: Open fractures; bone; trauma; method; treatment